Weekly Paclitaxel, Carboplatin, and Cetuximab as First-Line Treatment of Recurrent and/or Metastatic Head and Neck Squamous Cell Carcinoma for Patients Ineligible to Cisplatin-Based Chemotherapy: A Retrospective Monocentric Study in 60 Patients - Carinato, Hélène; Burgy, Mickaël; Ferry, Régine; Fischbach, Cathie; Kalish, Michal; Guihard, Sébastien; Brahimi, Youssef; Flesch, Henri; Bronner, Guy; Schultz, Philippe; Frasie, Véronique; Thiéry, Alicia; et al. (Frontiers in Oncology, 2021)
Objective: For most patients suffering from recurrent and/or metastatic head and neck squamous cell carcinoma (R/M HNSCC), chemotherapy is the main option after considering surgery and re-irradiation. Cetuximab combined with a platinum-fluorouracil regimen (EXTREME) has been the standard of care for over a decade. Nevertheless, a significant number of patients remains unfit for this regimen because of age, severe comorbidities or poor Performance Status. The aim of this study is to investigate an alternative regimen with sufficient efficacy and safety. Methods: We reviewed retrospectively the medical charts of all patients treated with paclitaxel, carboplatin and cetuximab (PCC) at our institution. Eligibility criteria were: first-line R/M-HNSCC of the oral cavity, oropharynx, hypopharynx or larynx not suitable for local therapy, cisplatin and/or 5FU ineligibility, ECOG-PS: 0-2. PCC consisted of paclitaxel 80 mg/m2, carboplatin AUC 2 and cetuximab at an initial dose of 400 mg/m2 then 250 mg/m2, for 16 weekly administrations followed by cetuximab maintenance. The primary endpoint was overall survival (OS), secondary endpoints were overall response rate (ORR), progression free survival (PFS) and safety. Results: We identified 60 consecutive patients treated with PCC between 2010 and 2016 at our institution. Thirty-one patients (52%) were ECOG-PS 2. Fifty-five patients (92%) were cisplatin ineligible. ORR was 43.3% (95%CI: 30.8-55.8) and disease control rate was 65% (95%CI: 52.9-77.1). With a median follow-up of 35.7 months (IQR 28.6-48.8), median PFS was 5.8 months (95%CI: 4.5-7.2) and median OS was 11.7 months (95%CI: 7.5-14.8). For PS 0-1 patients, median OS was 14.8 months (95%CI: 12.2-21.7) while it was only 7.5 months (95%CI: 5.5-12.7) for PS 2 patients (p < 0.04). Grade III-IV toxicities occurred in 30 patients (50%). Most toxicities were hematologic. Six patients (10%) had febrile neutropenia. Non-hematologic toxicities were reported such as cutaneous toxicities, neuropathy, infusion-related reactions or electrolytes disorders. Conclusion: The weekly PCC regimen seems to be an interesting option in cisplatin-unfit patients. This study shows favorable PFS and OS when compared to what is achieved with the EXTREME regimen and a high controlled disease rate with predictable and manageable toxicities even in the more fragile population.